Analisis Hubungan Sikap dan Tuning dengan Kepatuhan Perawat dalam Ketepatan Identifikasi Pasien di Rumah Sakit X Kabupaten Banyuwangi Tahun 2024 - Wardhani, Lusyana Putri Kusuma; Imelida, Ica; Lailiyah, Syifa’ul; Damayanti, Nyoman Anita; Prayoga, Dian Santo (UI Scholars Hub, 2025)
Patient safety is a top priority in healthcare services, including in the prevention of identification errors. Accurate patient identification is one of the Patient Safety Goals mandated by the Joint Commission International (JCI) 2024. The issue addressed in this study is the low compliance of nurses with patient identification procedures at Hospital X in Banyuwangi Regency. This study aims to analyze the relationship between nurses’ attitudes and tuning with compliance in implementing patient identification. A quantitative approach with a cross-sectional design was used. Data on attitudes and tuning were collected through questionnaires, while compliance data were obtained from direct observations of 91 randomly selected nurses. The analysis showed a significant relationship between nurses’ attitudes and compliance with patient identification (p = 0.006), whereas tuning did not show a significant relationship (p = 1.00). Although most nurses had a positive attitude, inconsistencies were found between their attitudes and actions in the field. Therefore, it is recommended that practice-based training be provided, strict supervision by head nurses implemented, and patient identification technologies such as barcodes or Radio Frequency Identification (RFID) be utilized as innovations to improve compliance with procedures.